Напрями підвищення ефективності функціонування коксохімічних підприємств (на прикладі прат "Макіївкокс") - Вода, І.С.; Овчаренко, Т.В. (Економіка промисловості, 2013)
Досліджено структуру ефективності діяль-ності коксохімічних підприємств України за кри-те¬ріями ефективності та проведено аналіз конку-ренто¬спроможності. Розроблено заходи щодо підвищення ефективності діяльності виробництва коксохімічних підприємств на прикладі ПрАТ «Макіївкокс».
Ключові слова: ефективність діяльності
під¬при¬ємства, конкурентоспроможність, коксо-хіміч¬ні підприємства України, модернізація. Исследована структура эффективности деятельности коксохимических предприятий Украины по критериям эффективности и проведен анализ конкурентоспособности. Разработаны мероприятия по повышению эффективности деятельности производства коксохимических предприятий на примере ПрАТ «Макеевкокс».
Ключевые слова: эффективность деятельности предприятия, конкурентоспособность, коксохимические предприятия Украины, модернизация. At the present stage of economic and social development of Ukraine's economy steel industry, which provides 27% of the industrial production of the state generating about 40% of foreign exchange earnings in Ukraine and more than 10% of government revenue, is of great importance. Ukraine is one of the leading countries - producers of ferrous metals in the world in terms of steel production and the volume of exports of steel products. By-product-coking IndustryEnterprises of Ukraine is an integral component of metallurgical industrial complex, which also has close connection with other industries. The aim of this study is to determine promising ways of increasing the efficiency of coke plants by modernizing the production.
The structure of the effectiveness of by-product coke enterprises of Ukraine is based on the performance criteria. The measures of increasing the efficiency of production of by-product coke enterprises are developed by example of Private Joint Stock Company "Makiyivkoks".
The basic direction of innovative activity in the area of blast-furnace production is the restructuring of fuel base by the replacement of part of coke by less expensive sources of energy.
Two projects are offered: the reconstruction of separation distillation of crude benzene, and reconstruction of resinification processing plant.
Implementation of the project of reconstruction of separation distillation of crude benzene will considerably reduce energy costs, which will cut down the cost of manufactured products, and significantly improve the quality of products of the Private Joint Stock Company "Makiyivkoks".
Implementation of the project for the reconstruction of resinification processing plant will allow the company to expand production assortment, and significantly improve product quality at the Private Joint Stock Company "Makiyivkoks".
Keywords: efficiency of activity of an enterprise, competitiveness, by-product coke plants of Ukraine, modernization.